Star Trek online. - Stapleton, Dan (PC gamer)
Startdate: 2409.10 Thirty years after the events of Star Trek: Nemesis, the galaxy has become a very different, very dangerous place. The United Federation of Planets and the Klingon Empire are once again on the verge of all-out war (because let's face it: peace is boring). But this won't be like the Star Trek episodes where diplomats huddle around a negotiating table for an hour, calmly working through their cultural misunderstandings. This is more like the ones where the negotiations have failed--and it's time to set your phasers to kill.